2016
DOI: 10.1210/en.2015-1750
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-Induced CART (Cocaine- and Amphetamine-Regulated Transcript) Is a Novel Intraovarian Mediator of Obesity-Related Infertility in Females

Abstract: Obesity is considered detrimental to women's reproductive health. Although most of the attention has been focused on the effects of obesity on hypothalamic function, studies suggest a multifactorial impact. In fact, obesity is associated with reduced fecundity even in women with regular cycles, indicating that there may be local ovarian effects modulating fertility. Here we describe a novel mechanism for leptin actions directly in the ovary that may account for some of the negative effects of obesity on ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…In cows and ewes, CART is reported to be expressed in the ovary and present in ovarian follicular fluid (Kobayashi et al, 2004; Juengel et al, 2017). Moreover, in vitro experiments further supported that CART can inhibit basal and FSH-induced estradiol production in granulosa cells and may act as an important local autocrine/paracrine factor involved in the regulation of ovarian follicle development and steroidogenesis (Sen et al, 2007; Ma et al, 2016; Juengel et al, 2017). These pioneering findings, together with our convincing evidence showing that the expression and secretion of CART in chicken pituitary is regulated by GnRH (Figures 2–4), suggest that CART can act at different tier(s) of the hypothalamic-pituitary-gonadal axis (HPG) to regulate vertebrate reproduction (Kobayashi et al, 2004; True et al, 2013; Juengel et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In cows and ewes, CART is reported to be expressed in the ovary and present in ovarian follicular fluid (Kobayashi et al, 2004; Juengel et al, 2017). Moreover, in vitro experiments further supported that CART can inhibit basal and FSH-induced estradiol production in granulosa cells and may act as an important local autocrine/paracrine factor involved in the regulation of ovarian follicle development and steroidogenesis (Sen et al, 2007; Ma et al, 2016; Juengel et al, 2017). These pioneering findings, together with our convincing evidence showing that the expression and secretion of CART in chicken pituitary is regulated by GnRH (Figures 2–4), suggest that CART can act at different tier(s) of the hypothalamic-pituitary-gonadal axis (HPG) to regulate vertebrate reproduction (Kobayashi et al, 2004; True et al, 2013; Juengel et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…CART peptide encoded by CART gene was first discovered in abundance in the rat hypothalamus, in which it may act as a downstream effector of leptin with potent appetite-suppressing activity (Douglass et al, 1995; Gautvik et al, 1996; Kristensen et al, 1998; Elias et al, 2001). Besides the hypothalamus, CART is also expressed in other brain regions, the peripheral nervous system (PNS) and peripheral tissues of mammals including the anterior pituitary, ovary, and pancreas (Koylu et al, 1997; Jensen et al, 1999; Thim et al, 1999; Murphy et al, 2000; Kobayashi et al, 2004; Wierup et al, 2006; Ma et al, 2016), and is suggested to be involved in the regulation of many other physiological processes, such as drug reward and reinforcement, stress, pancreatic secretion, bone remodeling, and ovarian follicle development and steroidogenesis (Kobayashi et al, 2004; Elefteriou et al, 2005; Sen et al, 2007; Rogge et al, 2008; Abels et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(12) Others have also found that a high fat diet may increase follicular atresia. (11, 13, 15) However, a study in mice found no significant differences in serum AMH concentrations between those fed a low-fat or high-fat diet, suggesting that granulosa cell function may not be altered by high fat intake. (12) Studies of dietary fat and markers of ovarian reserve in humans are more limited.…”
Section: Discussionmentioning
confidence: 99%
“…Again, miRNAs related to leptin in fetal programming still remain a poorly studied area of research. Recently, Sinha et al studied a gestational diabetes murine model to investigate the epigenetic regulation of cocaine- and amphetamine-regulated transcript (CART), a gene which was previously found by this research group as a mediator of hyperleptinemia-induced infertility [132,133]. The whole set of combined epigenetic changes include (i) miRNAs, (ii) histone acetylation and methylation, and (iii) altered promoter methylation, switched on the CART promoter into hypersensitive to leptin during in utero fetal programming.…”
Section: Epigenetics Of Leptin In Fetal Programmingmentioning
confidence: 99%